Traveling pro les solutions to heat equation with a power-law nonlinearity - Arioua, Yacine; Benhamidouche, Nouredine (Université de M'sila, 2015)
We propose in this work a new approach to obtain a general form of self similar solutions to heat equation with a power-law nonlinearity. We use the ”traveling profiles method”. This method is inspired of the traveling wavelets method which belongs to the category of the particular methods. The traveling profiles method enables us to obtain many explicit exact solutions to this equation.
Keywords: Heat equation with a power-law nonlinearity; Traveling profiles method.